PENEBALAN DINDING SEL XILEM TANAMAN KEDELAI [Glycine max (L.) Merr.] var. GROBOGAN AKIBAT CEKAMAN GANDA INTERFERENSI TEKI (Cyperus rotundus L.) DAN KEKERINGAN - Darmanti, Sri (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2015)
Anatomical changes are good indicators used to know influence environmental stress on plant. The objective of this research is to study the multiple stress effect of  purple nutsedge  (Cyperus rotundus L.) interference and drough on  the xylem cell wall thickening of stems, roots and leaves of soybean [Glycine max (L.) Merr.] Var. Grobogan. This research was carried out using two experimental Completely Randomized Designs (CRD) (3X3), i.e. purple nutsedge interference (control, three and six  purple nutsedge) and drought stress (control, mild and severe).  The results showed that  multiple stress  purple nutsedge interference and drought led to the addition of xylem cell wall thickness of stem, root  and leaves .The higher level of interference and drought, xylem cell walls thicker. Keyword :  multiple stress, ROS, phenolic compound, lignin, xylem.